Implementación de un sistema de control de los parámetros que intervienen en un secador cilíndrico de Cacao - Jaya Chisaguano, Luis David (2022)
The present technological proposal intends to implement a control system in a cylindrical cocoa dryer, the main purpose is to obtain data of the factors that are involved in the system for which sensors were obtained that collected the correct information of the process, thus carrying out a compilation of data in the cloud, that is to say that it allowed to be a source of information for multiple studies that are intended to be implemented in the future, with the purpose of investigating the different ways of drying cocoa so that the requirements of the product to be processed are met. This control system allowed the drying to be carried out in the shortest possible time, so that the project directly benefits small producers, especially in the economic part, minimizing labor costs and thus allowing the drying to be perform efficiently. Finally, it was obtained as a result that the cocoa started with a humidity of 70.13% at a temperature of 20°C, by means of the control the temperature was raised to 60°C, which is the ideal temperature according to the INEN NTE176 standard, in three hours and fifteen minutes, the cocoa bean was dried and reached an ideal final humidity of 7%.